Crop Residue for Nutrient Cycling: Unlocking the Potential of Nature’s Leftovers - Singh, Arjun; Bana, R. S.; Pooniya, Vijay; Singh, Teekam; Jat, N. K. (Chronicle of Bioresource Management, 2024)
Crop residue recycling emerges as a sustainable and economically viable solution to the pressing challenges of soil nutrient depletion and environmental degradation in Indian agriculture. By harnessing the nutrient-supplying potential of surplus crop residues, farmers can reduce their reliance on chemical fertilizers, lower production costs, and enhance soil health. However, realizing this potential requires concerted efforts in policy support, technological innovation, and farmer education. As Indian agriculture continues to strive for agricultural sustainability and food security, integrating crop residue management into mainstream farming practices could serve as a cornerstone for achieving these goals. Embracing the wisdom of nature’s leftovers not only preserves the environment but also ensures the long-term viability of Indian agriculture.